Дизайн інтерʼєру технічно-допоміжних приміщень офтальмологічного відділення Лікарні Святого Миколая першого медоб’єднання Львова для дітей, вул. Пилипа Орлика, 4 - Смаль, Тетяна Михайлівна; Smal, Tetiana Mykhailivna (Національний університет "Львівська політехніка", 2024)
Бакалаврська робота присвячена створенню сучасного інтер’єру, прагненню створити комфортний та затишний простір, де маленькі пацієнти почуватимуться спокійно та безпечно. В першому розділі досліджено історію появи та тенденцію розвитку лікарень за кордоном, а також розвиток дитячих лікарень у Львові. Досліджено об’єкт проєктування та його особливості. У другому розділі важливим завданням було віднайти особливості дизайну інтер’єру дитячих лікарень. Отож, досліджено які чинники впливають, аби зробити якісний дитячий простір, його ергономічні норми, державні норми, безбар’єрність. В межах роботи проведено інтерв’ю із психологом, яке допомогло краще зрозуміти дітей різної вікової категорії. Проаналізовано різні медичні заклади із застосуванням сучасних елементів. У третьому розділі описано дизайн інтер’єру технічно-допоміжних приміщень офтальмологічного відділення лікарні Святого Миколая. Описано загальну концепцію інтер’єру - казковий ліс, поділ функціонального зонування відділенння, стилістику, композиційне та художньо-образне вирішення. Детально описано артоб’єкт “Сова” - як головна героїня інтер’єру лісу, матеріали, функція і головні мотиви. У четвертому розділі описується економічна частина проєкту та загальний кошторис. 3

Explanatory note to the diploma project for obtaining the first (bachelor's) level of higher education in the specialty 022 "Design". - Lviv Polytechnic National University of the Ministry of Education and Science of Ukraine, Lviv, 2025. The bachelor's thesis is dedicated to the creation of a modern interior, the desire to create a comfortable and cozy space where young patients will feel calm and safe. The first section examines the history of the emergence and development trend of hospitals abroad, as well as the development of children's hospitals in Lviv. The design object and its features are studied. In the second section, an important task was to find the features of the interior design of children's hospitals. So, the factors influencing the creation of a high-quality children's space, its ergonomic standards, state standards, and accessibility were investigated. As part of the work, an interview was conducted with a psychologist, which helped to better understand children of different age categories. Various medical institutions were analyzed using modern elements. The third section describes the interior design of the technical and auxiliary premises of the ophthalmology department of St. Nicholas Hospital. The general concept of the interior is described - a fairy-tale forest, the division of the functional zoning of the department, style, compositional and artistic-figurative solution. The art object “Owl” is described in detail - as the main character of the forest interior, materials, function and main motifs. The fourth section describes the economic part of the project and the total estimate.
Interior design of technical and auxiliary premises of the ophthalmology department at St. Nicholas Hospital of the First Medical Association of Lviv for Children, 4 Pylypa Orlyka St.
Keywords: 6.022.03.03; дитяча лікарня; дизайн інтер’єру; інтерв’ю; проєктування; ліс; стилістика; children's hospital; interior design; interview; design; forest; style